In defense of loose translations : an Indian life in a mainstream academic world - Cook-Lynn, Elizabeth (American Indian lives., 2018)
"In Defense of Loose Translations: An Indian Life in a Mainstream Academic World is Elizabeth Cook-Lynn's memoir that bridges personal and professional experiences of the provocative, and often controversial, writer who narrates the story of her intellectual life in the field of Indian Studies"--Provided by publisher